Association between serotonin transporter gene polymorphisms and increased suicidal risk among HIV positive patients in Uganda - Kalungi, Allan; Seedat, Soraya; Hemmings, Sian M. J.; Merwe, Lize van der; Joloba, Moses L.; Nanteza, Ann; Nakassujja, Noeline; Birabwa, Harriet; Serwanga, Jennifer; Kaleebu, Pontiano; Kinyanda, Eugene (BMC genetics, 2017)
Persons living with HIV/AIDS (PLWHA) are at an increased risk of suicide. Increased suicidal risk is a predictor of future attempted and completed suicides and has been associated with poor quality of life and poor adherence with antiretroviral therapy. Clinical risk factors have low predictive value for suicide, hence the interest in potential neurobiological correlates and specific heritable markers of suicide vulnerability. The serotonin transporter gene has previously been implicated in the aetiology of increased suicidal risk in non-HIV infected study populations and its variations may provide a platform for identifying genetic risk for suicidality among PLWHA. The present cross-sectional study aimed at identifying two common genetic variants of the serotonin transporter gene and their association with increased suicidal risk among human immunodeficiency virus (HIV)-positive adults in Uganda. Results: The prevalence of increased suicidal risk (defined as moderate to high risk suicidality on the suicidality module of the Mini Neuropsychiatric Interview (M.I.N.I) was 3.3% (95% CI, 2.0–5.3). The 5-HTTLPR was found to be associated with increased suicidal risk before Bonferroni correction (p-value = 0.0174). A protective effect on increased suicidal risk was found for the 5-HTTLPR/rs25531 SA allele (p-value = 0.0046)- which directs reduced expression of the serotonin transporter gene (5-HTT). Conclusion: The SA allele at the 5-HTTLPR/rs25531 locus is associated with increased suicidal risk among Ugandan PLWHA. Further studies are needed to validate this finding in Ugandan and other sub-Saharan samples.
Keywords: Suicidal risk; Serotonin transporter (5-HTT) gene polymorphisms; HIV/Aids; Uganda